Con Otros Ojos Para Ver - With Different Eyes to See - Murillo, Maria Jose; Noqanchis Collective; Portocarrero, Florencia (Peru; Artus; ICPNA, 2023)
With Different Eyes to See is the solo exhibition by Maria Jose Murillo, curated by Florencia Portcarrero, that this publication is based around. This exhibition highlights the artist's participation in the 2022 ICPNA Artus WIELS scholarship. This publication introduces textile as a medium that goes beyond the aesthetic, acting as a container of history, identity, and cultural dialogue.
Spanish; English
Keywords: Andean textiles; N4390-5098 Visual Arts. Exhibitions; Textile art; Peru